The effect of crosslink density on the cold crystallization behavior of polybutadiene elastomers - Arpan Datta Sarma; Erathimmanna Bhoje Gowd; Amit Das; Gert Heinrich (eXPRESS Polymer Letters)
This report presents an insightful investigation of the cold crystallization behavior of sulfur-crosslinked polybutadiene elastomers. The influence of crosslink density on the cold crystallization activities of sulfur-crosslinked polybutadiene rubber (BR) is investigated using differential scanning calorimetry, dynamic mechanical analysis, and X-ray techniques. A significant increase in storage modulus (E') is observed at a temperature just above the glass transition temperature (Tg). This behavior was found to be highly dependent on the crosslink density of the rubber. The dynamic mechanical behavior of the sulfur crosslinked BR is supported by further studies using differential scanning calorimetry and low-temperature X-ray diffraction. This study could contribute to a better understanding of the behavior of BR-containing tire tread rubbers at lower temperatures.